Introduction "Urban lives and protests in neoliberal times: Art, aesthetics and solidarity as possibilities" - Deltsou, Eleftheria; Tsibiridou, Fotini (The Greek Review of Social Research, 2018)
The introduction to this special issue explores theoretically the emergence of the cultural turn in contemporary social movements. Its focus on “possibility” as a broad array of culturally and politically disparate practices and ideas makes possible to discuss in the frame of contigency: the appearance of different forms of urban living and re-acting by focusing on visions of urban life that are activated by social movements; How these visions are put in practice; The already culturally available or newly imagined ways of relating in the new forms of social mobilization; The tactics, strategies, poetics, and rhetorics that social movements employ as they re-act against more or less authoritarian practices in neoliberal times. The case studies concern the following cities around the world: Bogota (Colombia), Los Angeles (U.S.A.), Istanbul (Turkey), Thessaloniki (Greece).